Combined therapy with the estrogen receptor ERα and IFNα-2b suppresses HBV replication by inducing GBP1 expression - Li, Yadi; Gong, Jiaojiao; Tan, Guili; Luo, Haiying; Hu, Xiaoxia; Qin, Bo (Frontiers in Immunology, 2026)
Pegylated interferon α-2b (peg IFNα-2b) is a first-line clinical drug for the treatment of chronic hepatitis B (CHB). It can effectively reduce HBsAg levels, improve clinical cure rates, and lower the incidence of HBV-associated hepatocellular carcinoma (HCC). Notably, females consistently exhibit a better early response to interferon therapy than males do. Previous studies have confirmed that the estrogen receptor ERα inhibits HBV transcription. However, reports on combined treatment with ERα and peg IFNα-2b for HBV infection are limited. Hepatocyte RNA-seq analysis revealed that both ERα elevation and IFNα stimulation can lead to increased expression of GBP1. GBP1 has been reported to inhibit several bacteria and HCV, but evidence of its effect on HBV infection is insufficient.We systematically investigated the roles of ERα, peg IFNα-2b, and GBP1 in modulating HBV infection in an HBV-infected HepG2-NTCP cell model. Molecular dynamics simulation and molecular docking methods were employed to analyze the stability and interaction sites of the ERα and GBP1 complex. Finally, we examined the RNA and protein levels of GBP1 and ERα in the peripheral blood of CHB patients treated with peg IFNα-2b.GBP1 was induced by costimulation with ERα and peg IFNα-2b. The combination of ERα and peg IFNα-2b enhanced the inhibition of HBV replication, which might be achieved by promoting GBP1 expression and altering its cellular distribution. GBP1 was highly expressed in the PBMCs and liver tissues of CHB patients and was specifically positively correlated with ERα. Interestingly, GBP1 was enriched in the NOD-like signalling pathway, which activates the host immune response.Our study demonstrated that the combination of ERα and peg IFNα-2b exerts antiviral effects by mediating the high expression of GBP1. These findings reveal the associations among ERα, peg IFNα-2b, and innate antiviral immunity, which target GBP1.